PERAN CAREGIVER TERHADAP EFEKTIVITAS MODIFIKASI MAKANAN PADA LANSIA - Nafisah Gita Ayu Sakila; Dinasti Pudang Binoriang (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2024)
Elderly people are individuals who have reached the age of 60 years and over. The elderly experience physical, physiological and mental decline. These changes are related to each other. Unbalanced nutritional intake will affect the nutritional status of the elderly. This situation is called malnutrition. To see the effect of modifying food texture in the elderly to increase appetite and thereby reduce the risk of malnutrition. This study uses a descriptive case study method. The results of the Mini Nutritional Assessment (MNA) before the intervention was given showed a score of 22.5. After the intervention was carried out twice a month, modification of food texture was found to have no effect on the appetite level of the elderly. The results of the study showed that modification of food texture had no effect on appetite levels because the time period was not optimal.